2020
DOI: 10.1016/j.parepi.2020.e00188
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malaria parasitaemia in school-aged children and pregnant women in endemic settings of sub-Saharan Africa: A systematic review and meta-analysis

Abstract: Despite increased malaria control efforts, school-aged children (5–14 years) have higher a malaria prevalence compared to children under-five. In high-transmission settings, up to 70% of school-aged children harbour malaria parasitaemia and therefore contribute significantly to the reservoir for transmission. A systematic review was performed to explore the correlation between the malaria parasite carriage in pregnant women and school-aged children living in similar endemic settings of sub Saharan Africa to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 70 publications
0
25
0
1
Order By: Relevance
“…Even though a number of factors may contribute to the fluctuation of parasitaemia level overtime in symptomatic patients, the geometric mean of microscopically detectable parasitaemia levels could be used to explain the finding of this study [ 24 ]. The major factor that mainly contributed for higher parasitaemia level in SAC is delayed acquisition of protective immunity during this immunological transition age making this age group more vulnerable to malaria infection than adults [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though a number of factors may contribute to the fluctuation of parasitaemia level overtime in symptomatic patients, the geometric mean of microscopically detectable parasitaemia levels could be used to explain the finding of this study [ 24 ]. The major factor that mainly contributed for higher parasitaemia level in SAC is delayed acquisition of protective immunity during this immunological transition age making this age group more vulnerable to malaria infection than adults [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though a number of factors may contribute to the uctuation of parasitaemia level overtime in symptomatic patients, the geometric mean of microscopically detectable parasitemia levels could be used to explain the nding of this study (Shekalaghe et al, 2005). The major factor that mainly contributed for higher parasitaemia level in SAC is delayed acquisition of protective immunity during this immunological transition age making this age group more vulnerable to malaria infection than adults (Makenga et al, 2020).…”
Section: Allelic Polymorphism Of Block 2 Region Of Msp-1 Gene and Their Level Of Severity Spatial And Seasonal Featuresmentioning
confidence: 98%
“…A study conducted in Malawi revealed that schoolaged children (SAC) were as susceptible as under-five children to Plasmodium species [8]. As compared to pregnant women, SAC were at two-fold increased risk for malaria and 1% increase in malaria among pregnant mothers was equivalent to 4% increase in malaria among SAC in sub-Saharan Africa (SSA) [9]. The other explanation for high prevalence of malaria among SAC was the duration of persistent infection.…”
Section: Introductionmentioning
confidence: 99%